First musculotendinous grafts with motorizing function in paralyzed areas - Pera Erro, Enrique (Cirugía del Uruguay, 1979)
In 1973, the author performed, .for the first time in Uruguay, a complete transplant of skeletal musculotendin, ms units, as autografts.